The Implementation of Al-Kamal Methods to Enhance the Proficiency in Reading Kitab Kuning at Mambaul Ulum Islamic Boarding School, Paiton, Probolinggo - Nabihah, Azmiyatun; Wijaya, Mualim; Khotimah, Isnol (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
The learning of the yellow book in Islamic boarding schools is still dominated by the Al-Kamal methods, which focus on understanding Arabic grammar and translating texts. However, this method is often less effective in improving students' speaking and writing skills and is considered less attractive. This problem is a challenge in maintaining the effectiveness of learning the yellow book in the modern era. This study aims to analyze the effectiveness of the Al-Kamal methods in learning the yellow book and explore the challenges faced in its application. The research method used is a qualitative approach with observation, interview, and document analysis techniques in several Islamic boarding schools that still apply this method. The results of the study show that the Nahwu and Tarjamah methods are effective in building a systematic understanding of Arabic grammar, but have limitations in improving the productive skills of Arabic and are less attractive to students. Other factors that affect its effectiveness include a lack of teaching innovation and a lack of integration with modern learning methods. The implication of this research is the need for innovation in learning the yellow book by combining this traditional method with interactive approaches, educational technology, and contextual methods so that learning is more effective and attractive for students in the digital era.